2021
DOI: 10.1038/s41598-021-89981-z
|View full text |Cite
|
Sign up to set email alerts
|

The miR-378c-Samd1 circuit promotes phenotypic modulation of vascular smooth muscle cells and foam cells formation in atherosclerosis lesions

Abstract: MicroRNAs have emerged as key regulators in vascular diseases and are involved in the formation of atherosclerotic lesions. However, the atherosclerotic-specific MicroRNAs and their functional roles in atherosclerosis are unclear. Here, we report that miR-378c protects against atherosclerosis by directly targeting Sterile Alpha Motif Domain Containing 1 (Samd1), a predicted transcriptional repressor. miR-378c was strikingly reduced in atherosclerotic plaques and blood of acute coronary syndrome (ACS) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…It is also consistent with a recent finding that both up-and down-regulation of multiple pathways was seen in SAMD1 KO ES cells, including up-regulation of muscle cell migration [5]. In contrast, another study found that upregulation rather than downregulation of SAMD1 caused phenotype changes in VSMCs [3]. In apoE-/-mice after 16 weeks on HFD, medial SMC markers are reduced and some medial SMCs are expressing CD68 [52], suggesting additional phenotype changes that correlate with reduced SAMD1 staining.…”
Section: Samd1 In the Mediasupporting
confidence: 92%
See 4 more Smart Citations
“…It is also consistent with a recent finding that both up-and down-regulation of multiple pathways was seen in SAMD1 KO ES cells, including up-regulation of muscle cell migration [5]. In contrast, another study found that upregulation rather than downregulation of SAMD1 caused phenotype changes in VSMCs [3]. In apoE-/-mice after 16 weeks on HFD, medial SMC markers are reduced and some medial SMCs are expressing CD68 [52], suggesting additional phenotype changes that correlate with reduced SAMD1 staining.…”
Section: Samd1 In the Mediasupporting
confidence: 92%
“…Only 2 days after injury, there is a 60% reduction in the number of medial SMCs [28]; medial SMCs rapidly dedifferentiate, migrate to the intima, and proliferate such that at two weeks, about 80% of cells in the developing neointima are SMC, many of these have differentiated to macrophage-like foam cells [29], [30]. We thus hypothesize that SAMD1 expressed by intimal SMCs is the LDL binding molecule [2], [3], that gradually comes into effect in spontaneous lesions as intimal SMCs migrate and proliferate, starting between weeks 8 and 12 [31].…”
Section: Treatment Effectmentioning
confidence: 95%
See 3 more Smart Citations